Detection of the common genetic abnormalities by reverse transcriptase-polymerase chain reaction (rt-pcr) in children with acute leukemia at Hue Central hospital - Chau, Van Ha; Nguyen, Duy Thang; Phan, Thi Thuy Hoa; Pham, Hoang Hung; Phan, Xuan Mai; Watanabe, Kazuyo (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2016)
Background: Acute Leukemia (AL) is a heterogenerous disease. Recent advances in cytogenetics and molecular genetics have made it possible to identify the genetic abnormalities with prognostic and therapeutic significance. In Vietnam, the diagnostic molecular screening for AL is still limited. Objective: To detect the genetic abnormalities among the children with AL admitted to Hue Central Hospital. Methods: This is a single institutional prospective study of 50 children newly diagnosed with AL from May 2012 to January 2015 at Hue Central Hospital. The molecular genetic screening test using Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) was performed to detect gene fusions. Results: Of 50 patients analyzed, there were 38 children with ALL and 12 children with AML, median age was 3.9 year (range 2 months to 15 years). Regarding ALL The frequencies of the genetic abnormalities were as follow: 9(23.7%) with t(12;21)/TEL-AML1, 2(5.3%) with t(9;22)/BCR-ABL, 3(7.9%) with t(4;11)/ MLL-AF4, 4 (10.5%) with t(1,19)/E2A-PBX1. Regarding AML The frequencies were: 1(8.3%) with t(8;21)/ AML1-ETO, 2(16.6%) with t(15;17)/PML-RARA, 1(8.3%) with t(16,16)/CBFB-MYH11, 2 (16.6%) with t(9;11)/ MLL-AF9. 15,8% of ALL and 25,0% of AML had been chromosomal abnormalities. Hyperdiploidy were 5,3% of ALL and 16,6% of AML. Conclusion: The frequencies of the genetic abnormalities of our patients are higher than that in the reported literatures. Our sample size is small; therefore, further study with larger sample size will be necessary to have the true frequencies. RT-PCR is a useful and rapid tool to detect genetic abnormalities to improve the ability to accurately and rapidly risk-stratify children with AL.